Asymptomatic immune responders to Leishmania among HIV positive patients. - Laura Botana; Ana Victoria Ibarra-Meneses; Carmen Sánchez; Alicia Castro; Juan Victor San Martin; Laura Molina; Jose Manuel Ruiz-Giardin; Eugenia Carrillo; Javier Moreno (Public Library of Science (PLoS), 2019)
Concomitant infection with human immunodeficiency virus (HIV) and the Leishmania parasite is a growing public health problem, the result of the former spreading to areas where the latter is endemic. Leishmania infection is usually asymptomatic in immunocompetent individuals, but the proportion of HIV+ individuals in contact with the parasite who remain asymptomatic is not known. The aim of the present work was to examine the use of cytokine release assays in the detection of asymptomatic immune responders to Leishmania among HIV+ patients with no previous leishmaniasis or current symptomatology. Eighty two HIV+ patients (all from Fuenlabrada, Madrid, Spain, where a leishmaniasis outbreak occurred in 2009) were examined for Leishmania infantum infection using molecular and humoral response-based methods. None returned a positive molecular or serological result for the parasite. Thirteen subjects showed a positive lymphoproliferative response to soluble Leishmania antigen (SLA), although the mean CD4+ T lymphocyte counts of these patients was below the normal range. Stimulation of peripheral blood mononuclear cells (PBMC) or whole blood with SLA (the lymphoproliferative assay and whole blood assay respectively), led to the production of specific cytokines and chemokines. Thus, despite being immunocompromised, HIV+ patients can maintain a Th1-type cellular response to Leishmania. In addition, cytokine release assays would appear to be useful tools for detecting these individuals via the identification of IFN-γ in the supernatants of SLA-stimulated PBMC, and of IFN-γ, MIG and IL-2 in SLA-stimulated whole blood. These biomarkers appear to be 100% reliable for detecting asymptomatic immune responders to Leishmania among HIV+ patients.